Ecological stoichiometry: An elementary approach using basic principles. (14th November 2013) - Hessen, Dag O.; Elser, James J.; Sterner, Robert W.; Urabe, Jotaro
Abstract : Based on the observation that organism‐specific elemental content creates ecologically relevant mismatches such as between plant and animal tissue, it was postulated—and experimentally verified—that this would profoundly affect trophic efficiency and nutrient fluxes in ecosystems. From its beginnings as a Daphnia ‐centered perspective, the field of ecological stoichiometry (ES) has widened to include many organism groups, and ecosystem types, and the questions it addresses have broadened. We address some of the development of ES in aquatic sciences especially over the past 10 yr, focusing on homeostasis and mass balance in the consumer, and its effect on trophic efficiency and nutrient recycling in aquatic communities. We also discuss how ES has provided novel insights into genomic, proteomic, and cellular responses at one end of the biological scale as well as into large‐scale effects related to biogeochemical couplings at the ecosystem level. The coupling of global C, N, and P cycles via their biotic interactions and their responses to climate change accentuate ES as an important toolkit for ecosystem analysis. We also point to some of the major topics and principles where ES has provided new insights. For each of these topics we also point to some novel directions where the ES concepts likely will be useful in understanding and predicting biological responses.